2003
DOI: 10.1136/thorax.58.10.851
|View full text |Cite
|
Sign up to set email alerts
|

Can a self-management programme delivered by a community pharmacist improve asthma control? A randomised trial

Abstract: Background: No randomised studies have addressed whether self-management for asthma can be successfully delivered by community pharmacists. Most randomised trials of asthma self-management have recruited participants from secondary care; there is uncertainty regarding its effectiveness in primary care. A randomised controlled study was undertaken to determine whether a community pharmacist could improve asthma control using self-management advice for individuals recruited during attendance at a community pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
159
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(165 citation statements)
references
References 15 publications
3
159
0
3
Order By: Relevance
“…[31][32][33] Briefly, in Portugal, the health system is public and universal, but the pharmacies are private with guaranteed universal access. As such, the community pharmacy is in an optimal place to medication and self-reported the pathology, we could not confirm that AR patients were not in fact ARA patients.…”
Section: Limitationsmentioning
confidence: 99%
“…[31][32][33] Briefly, in Portugal, the health system is public and universal, but the pharmacies are private with guaranteed universal access. As such, the community pharmacy is in an optimal place to medication and self-reported the pathology, we could not confirm that AR patients were not in fact ARA patients.…”
Section: Limitationsmentioning
confidence: 99%
“…These factors have already been shown to be an important barrier to the achievement of good asthma control, as prescribing an appropriate asthma control treatment may not be successful when the patient uses the medication inappropriately [6][7][8][9]. Only a few well-designed studies have investigated the effect of pharmacist care on asthma patients to date [10][11][12][13][14][15]. These studies have shown improvements in peak flow [12][13][14][15], asthma severity [10,13], symptom scores [11], drug utilisation [10,[12][13][14] and humanistic outcomes (e.g.…”
mentioning
confidence: 99%
“…Only a few well-designed studies have investigated the effect of pharmacist care on asthma patients to date [10][11][12][13][14][15]. These studies have shown improvements in peak flow [12][13][14][15], asthma severity [10,13], symptom scores [11], drug utilisation [10,[12][13][14] and humanistic outcomes (e.g. quality of life, asthma knowledge) [10,[12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies involving community pharmacy-led asthma interventions have demonstrated a positive impact on patients' asthma-related quality of life and peak expiratory flow rates [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%